Heterogeneous doped iron phosphate, preparation method thereof and heterogeneous doped lithium iron phosphate
During the preparation process of lithium iron phosphate positive electrode material, the co-precipitation and secondary doping technology of titanium ions are used to form a shell-core structure with a higher surface doping ion content than the inside, which solves the problems of insufficient doping uniformity and efficiency in the prior art, and significantly improves the electrical properties of the material.
Patent Information
- Application Number
- CN202411950559.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art is difficult to ensure uniformity and efficiency of the doping effect when doping metal ions in lithium iron phosphate positive electrode materials, resulting in room for improvement in electrical performance.
By adding titanium ions to the iron source solution or the phosphorus source solution in an ionic form during the iron phosphate generation reaction, uniform co-precipitation and distribution of titanium elements are achieved, and a secondary doping additive is added to the surface of the iron phosphate dihydrate after transformation, forming a shell-core structure with a surface doped ion content higher than that of the inside.
The electrical properties of lithium iron phosphate positive electrode materials were improved, including 0.1C discharge capacity ≥162mAh/g, 1C discharge capacity ≥150mAh/g, and 10C discharge capacity ≥135mAh/g, significantly improving capacity and rate performance.
Smart Images

Figure CN119637825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of battery-grade iron phosphate, and in particular to a heterogeneously doped iron phosphate, a preparation method thereof and heterogeneously doped lithium iron phosphate. Background Art
[0002] Lithium iron phosphate positive electrode material has the advantages of long life, high discharge specific capacity, high safety, non-toxicity, and wide source of raw materials. With the advancement of overall battery technology, the application scope of lithium iron phosphate has been further expanded. It has absolute market and influence in the field of lithium-ion battery energy storage, and has also surpassed ternary batteries in the field of power batteries, with a market share of more than 70%.
[0003] The technological progress of lithium iron phosphate batteries has directly promoted the overall improvement of the performance of its positive electrode materials. The key indicators of the materials, such as energy density, compaction performance, rate performance, and cycle life, have all been improved to varying degrees. The existing technology for the research of lithium iron phosphate positive electrode materials focuses on optimizing and improving chemical indicators, physical indicators, and electrochemical indicators, and the influence of element doping in chemical indicators is very obvious.
[0004] Doping certain metal ions into the LiFePO4 lattice can promote the production of favorable defects in the material's lattice, and doping elements with different electronic structures can improve the migration channel of lithium ions, reduce the resistance to the diffusion of lithium ions along a one-dimensional path, and increase the rate of lithium ion migration inside lithium iron phosphate, thereby improving the cycle performance and rate performance of the LiFePO4 material.
[0005] In the prior art, metal ion doping is mostly achieved during the preparation of lithium iron phosphate, that is, doping ions are added during the mixed sand grinding of iron phosphate and lithium carbonate. The doping ions are mostly added in solid form. Affected by the efficiency of solid-solid reaction, the doping effect still needs to be improved.
[0006] There are also some existing technologies that combine the addition of doping ions with the preparation process of ferric phosphate in order to improve the doping uniformity and doping effect. That is, the doping ions are prepared into a solution and mixed with an iron source raw material liquid or a phosphorus source raw material liquid, and then participate in the reaction of preparing ferric phosphate with a phosphorus source and an iron source, so as to ensure the uniformity of doping and improve the doping effect through liquid phase doping.
[0007] Among them, it is more typical to combine the preparation process of titanium doping and iron phosphate. This is because the preparation process of iron phosphate often uses titanium-containing ferrous sulfate as a raw material source. Titanium-containing ferrous sulfate is directly used to participate in the reaction to prepare iron phosphate, which simplifies the impurity removal process of ferrous sulfate raw material liquid, and introduces titanium doping ions at the same time, which is a more efficient and energy-saving doping method. The Chinese patent with publication number CN117756076 A discloses a titanium-doped anhydrous iron phosphate material and its preparation method and application. The titanium-containing ferrous sulfate raw material liquid and the titanium-free ferrous sulfate raw material liquid are mixed, and the titanium-doped anhydrous iron phosphate material is obtained by aging, rinsing, drying and sintering with an oxidant and a phosphorus source. However, the titanium-containing ferrous sulfate raw material liquid used in the patent is directly dissolved by titanium dioxide byproducts, and the impurity ions are not purified. Finally, the impurity ions will enter the iron phosphate, causing the impurity content to increase. In a preparation method of battery-grade titanium-doped ferric phosphate disclosed in a Chinese patent with publication number CN118495494 A, ferrous sulfate produced as a by-product of titanium dioxide is used as a raw material, and a titanium ion dopant is introduced after purification. Impurities in the ferrous sulfate are effectively controlled, but the titanium introduced into the by-product ferrous sulfate of titanium dioxide is mainly in the form of metatitanic acid, titanium dioxide, etc. These components are difficult to dissolve to form titanium ions, and it is impossible to replace iron in the ferric phosphate lattice during the doping process. Therefore, the doping uniformity is difficult to control.
[0008] In summary, neither solid-phase doping nor ionic doping in the prior art can guarantee the doping effect well, and the electrical properties of the lithium iron phosphate positive electrode material finally prepared still have much room for improvement. Summary of the invention
[0009] The first object of the present invention is to provide a method for preparing heterogeneously doped iron phosphate, which can prepare a precursor iron phosphate of a lithium iron phosphate positive electrode material with excellent electrical properties.
[0010] The second object of the present invention is to provide a heterogeneously doped iron phosphate, and the lithium iron phosphate positive electrode material prepared by using the iron phosphate has excellent electrical properties.
[0011] The third object of the present invention is to provide a heterogeneously doped lithium iron phosphate having excellent electrical properties.
[0012] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0013] A method for preparing heterogeneously doped iron phosphate comprises the following steps:
[0014] S1. Preparation of raw material solution: prepare an iron source into an iron source solution, and prepare a phosphorus source into a phosphorus source solution; prepare a primary doping auxiliary agent containing titanium ions into a solution and add it to the iron source solution or the phosphorus source solution, mix them evenly and set aside for use; wherein, the iron source is ferrous sulfate, and the phosphorus source is industrial-grade monoammonium phosphate, and the phosphorus source solution prepared from the industrial-grade monoammonium phosphate is adjusted to a neutral pH value using ammonia water;
[0015] S2 mixing reaction: adding the iron source solution containing titanium ions, phosphorus source solution and oxidant prepared in step S1, or the phosphorus source solution containing titanium ions, iron source solution and oxidant to the reactor in proportion for rapid reaction; after the reaction, filtering and washing the slurry to prepare titanium-doped amorphous iron phosphate; wherein the oxidant is selected from oxygen, ozone or hydrogen peroxide; preferably hydrogen peroxide;
[0016] S3 aging and crystallization: adding water to the titanium-doped amorphous ferric phosphate prepared in step S2 to prepare a slurry, and adding a phosphoric acid solution to the slurry; gradually heating the slurry to perform aging and crystallization, and after the crystallization is completed, titanium-doped ferric phosphate dihydrate is prepared;
[0017] S4 secondary doping: uniformly adding a secondary doping aid to the titanium-doped ferric phosphate dihydrate prepared in step S3 to form a secondary doping ferric phosphate dihydrate; the secondary doping aid contains a secondary doping element, and the secondary doping element is selected from at least one of titanium, vanadium or niobium.
[0018] S5 drying and calcining: the secondary doped ferric phosphate dihydrate obtained in step S4 is dehydrated and dried, and then calcined at high temperature to form heterogeneous doped ferric phosphate.
[0019] When the lithium iron phosphate positive electrode material is working, Li + The migration between the positive and negative electrodes forms a current, and the unit cell structure of lithium iron phosphate causes Li + The movement distance is shortened and the movement is restricted; the Li + The inventors further studied the crystal structure of lithium iron phosphate and found that the Li + The more difficult it is to migrate to the surface, the more difficult it is to migrate to the surface. Based on this, the present invention creatively designs the Li + Migration channels are more than internal Li + The technical concept of migration channel to achieve the improvement of Li + The purpose of mobility and migration speed is further designed.
[0020] Firstly, in the process of the ferric phosphate formation reaction, the primary doping element titanium is added in the form of ions, so that titanium and iron can be co-precipitated, so that the titanium element can effectively replace the iron element in the ferric phosphate lattice. At the same time, since the titanium ion is added in the liquid phase reaction process, the uniform distribution of the titanium element in the ferric phosphate lattice can be ensured, and the uniformity of titanium doping can be ensured;
[0021] Secondly, in the present invention, after the titanium-doped amorphous ferric phosphate is transformed into titanium-doped ferric phosphate dihydrate, a secondary doping aid is uniformly added, so that the secondary doping aid can be physically mixed with the titanium-doped ferric phosphate dihydrate and distributed on the surface of the titanium-doped ferric phosphate dihydrate;
[0022] Furthermore, after the secondary doping aid is added, the titanium-doped ferric phosphate dihydrate is dried and dehydrated, and then calcined at high temperature. The secondary doping aid distributed on the surface of the titanium-doped ferric phosphate dihydrate achieves particle melting growth under high-temperature sintering conditions, and the secondary doping aid in contact with the surface of the iron phosphate is further dispersed to the surface of the iron phosphate particles under the action of high temperature, thereby increasing the doping ion content of the surface of the iron phosphate particles, forming a shell-core structure in which the surface doping ion content is higher than that of the interior.
[0023] The secondary doping aid of the present invention is selected from compounds containing titanium, vanadium or niobium. The compounds containing titanium, vanadium or niobium can be doped on the surface of iron phosphate particles to achieve the purpose of replacing iron ions and lithium ions in the lithium iron phosphate structure with titanium ions, vanadium ions or niobium ions after preparing lithium iron phosphate, so that the lithium iron phosphate lattice is distorted and defects are generated, thereby improving the Li + The diffusion channels can improve the electrochemical performance.
[0024] The iron phosphate particles prepared by the above method of the present invention are further prepared by a high-temperature solid phase process to obtain a lithium iron phosphate material. Since titanium ions are co-precipitated and doped in the form of ions in the iron phosphate reaction process, the uniform and smooth internal migration channels are ensured; more importantly, since the content of doped ions on the surface of the iron phosphate is higher than that in the interior, it is ensured that the migration channels on the surface of the lithium iron phosphate crystal cell formed are more than those in the interior, which can better ensure the Li + The migration amount and migration rate of lithium iron phosphate positive electrode materials are effectively improved.
[0025] Preferably, the primary doping aid is one or more of titanyl sulfate, titanium tetrachloride, tetrabutyl titanate, and titanium citrate.
[0026] The titanium-containing compound can form titanium ions in the solution. Using the titanium-containing compound as a primary doping aid can ensure that the titanium element co-precipitates with the iron phosphate in the form of ions during the formation reaction of the iron phosphate and is uniformly and stably doped in the iron phosphate.
[0027] Further preferably, the dosage of the primary doping aid is controlled so that the titanium content in the prepared titanium-doped amorphous ferric phosphate is 500 to 3000 ppm.
[0028] Preferably, the preparation method of the iron source solution in step S1 is: the ferrous sulfate by-product of titanium dioxide is configured into a solution, the pH value is adjusted to 2.8-5.5 by a pH regulator to carry out an impurity removal reaction, and after the impurity removal reaction is completed, the precipitate is filtered and separated to obtain the iron source solution.
[0029] In order to reduce costs, the present application selects ferrous sulfate produced as a by-product of titanium dioxide as the iron source for preparing ferric phosphate. Since ferrous sulfate produced as a by-product of titanium dioxide contains sulfuric acid and other metal impurities, these impurities are removed before the ferric phosphate formation reaction. The present application selects to use a pH adjuster to adjust the pH value to 2.8-5.5 to remove the sulfuric acid and other metal impurities contained in the ferrous sulfate produced as a by-product of titanium dioxide. Preferably, the pH adjuster of the present application is one or more of ammonia water, sodium hydroxide, sodium carbonate, monoammonium phosphate, diammonium phosphate, iron powder, and ferric hydroxide.
[0030] The present application chooses to first remove the metal impurities in the ferrous sulfate by-product of titanium dioxide to obtain an iron source solution, and then add a primary doping aid containing titanium ions to the iron source solution. The purpose is to remove the titanium-containing compounds (which cannot dissolve to produce titanium ions) contained in the original titanium dioxide by-product ferrous sulfate, and then introduce titanium ions to ensure that it is titanium ions that are co-precipitated with iron phosphate, thereby achieving the purpose of replacing the iron element in the iron phosphate unit cell with the titanium element to establish more lithium ion migration channels.
[0031] Preferably, the mixing reaction in step S2 is carried out in a microchannel tubular reactor. In the tubular reactor, the materials are in a turbulent state, and the mass transfer and heat transfer efficiency are high, so that the reaction can proceed quickly, which is conducive to the rapid and uniform combination of titanium, iron and phosphorus.
[0032] Preferably, the molar ratio of the phosphorus source, hydrogen peroxide and iron source added to the microchannel tubular reactor satisfies: P:H2O2:Fe=1.0:0.55~0.8:1.0~1.4; after the reaction is completed, the slurry first enters the homogenizing reactor, and the phosphorus source solution is added to the homogenizing reactor so that the final P:Fe involved in the reaction is 1:0.95~1.05; after the reaction is completed, the slurry is filtered and washed to prepare titanium-doped amorphous iron phosphate.
[0033] The present invention controls the iron salt solution and hydrogen peroxide in the tubular reactor to be slightly excessive, which is beneficial to stably control the combination of trivalent iron ions and phosphate radicals, avoids the formation of precipitation of ferrous ions, and affects the quality of iron phosphate. Further, after the reaction is completed, a homogenizing reactor is used as a further reaction of the material at the outlet of the carrying reactor, and the amount of phosphate is further supplemented in the homogenizing reactor, so that the unreacted iron salt solution can continue to react, promote the continued growth of iron phosphate crystals, effectively control the particle size of iron phosphate, and improve the subsequent washing efficiency.
[0034] Preferably, in step S3, the titanium-doped amorphous ferric phosphate is slurried with water to obtain a slurry with a solid content of 8-15%, and 85% phosphoric acid with a solid mass of 8-14% is added to the slurry. The slurry is gradually heated and aged and crystallized. The crystallization conditions control the crystallization temperature to 90-95°C and the crystallization time to 1-2h.
[0035] Preferably, the dosage of the secondary doping auxiliary agent is controlled so that the content of the secondary doping element in the final product, heterogeneously doped iron phosphate, is 500-3000 ppm.
[0036] Preferably, when the secondary doping element is titanium, the secondary doping aid is one or more of titanyl sulfate, titanium tetrachloride, tetrabutyl titanate, titanium citrate, nano rutile titanium dioxide, nano anatase titanium dioxide, and metatitanic acid; preferably, the secondary doping aid is one or more of nano rutile titanium dioxide, nano anatase titanium dioxide, and metatitanic acid;
[0037] Since the secondary doping is added after aging and crystallization to form titanium-doped dihydrate iron phosphate, it can only be added to the surface of the titanium-doped dihydrate iron phosphate particles. Therefore, it can be added in ionic form or solid form. Preferably, the present application selects one or more of nano-rutile titanium dioxide, nano-anatase titanium dioxide, and titanic acid with obvious cost advantages to introduce titanium element on the surface of iron phosphate.
[0038] When the secondary doping element is vanadium, the secondary doping aid is one or more of ammonium metavanadate, vanadium pentoxide, and vanadyl sulfate;
[0039] When the secondary doping element is niobium, the secondary doping aid is one or more of niobic acid, niobium pentoxide, niobium oxalate, and ammonium niobium oxalate.
[0040] Similarly, taking into account the introduction method and cost of the doping elements, the above-mentioned vanadium-containing secondary doping aid and niobium-containing secondary doping aid are selected.
[0041] Preferably, in step S4, when the secondary doping aid is non-water-soluble or has extremely poor solubility in water, it is added in solid phase form and directly added to the slurry containing titanium-doped ferric phosphate dihydrate obtained after the crystallization in step S3, and then the slurry is filtered and washed to obtain the secondary doped ferric phosphate dihydrate;
[0042] In step S4, when the secondary doping aid is water-soluble, it is added in the form of a solution, and the slurry containing titanium-doped ferric phosphate dihydrate after the crystallization in step S3 is filtered and washed to obtain a titanium-doped ferric phosphate dihydrate solid phase; the solution containing the secondary doping aid is directly added to the titanium-doped ferric phosphate dihydrate solid phase in an atomized form, or the solution containing the secondary doping aid is introduced into a dehydration and drying device in an atomized form together with the titanium-doped ferric phosphate dihydrate solid phase to obtain the secondary doped ferric phosphate dihydrate.
[0043] In order to ensure that the secondary doping elements can be more evenly distributed on the surface of titanium-doped iron phosphate dihydrate, this application is designed:
[0044] When the secondary doping aid is insoluble in water or has very poor solubility in water, when it is added in the form of a solid phase, such as nano-rutile titanium dioxide, nano-anatase titanium dioxide, and titanic acid, it is selected to be added to the slurry that has not been filtered and washed after the aging and crystallization in step S3. The solid material can be better dispersed in the slurry, and the solid-phase secondary doping aid can eventually enter the iron phosphate and will not be filtered out. After the solid-phase secondary doping aid is evenly mixed, filtering, washing, drying, calcining and other processes are performed.
[0045] When the secondary doping aid is easily soluble in water, it is added in the form of a solution, such as ammonium metavanadate, vanadium pentoxide, vanadyl sulfate, etc., and is added after the crystallization in step S3 is completed and filtered and washed. It can be added directly to the filter cake in the form of a solution spray, or it can be added to the drying device together with the filter cake in the form of a solution spray. It is preferably added to the drying device together with the filter cake to achieve uniform mixing of the doping elements dissolved in the solution and the iron phosphate particles as much as possible. If the secondary doping aid that is easily soluble in water is directly added to the slurry after aging and crystallization, it may be filtered out due to the dissolution of the doping elements in the water, resulting in it not being able to enter the iron phosphate product.
[0046] Specifically, when the secondary doping aid is selected from one or more of ammonium metavanadate, vanadium pentoxide, and vanadyl sulfate; desalted water or hydrochloric acid or nitric acid with a molar concentration of 0.01-0.1% is used to dissolve the secondary doping aid, and the vanadium ion concentration in the secondary doping aid solution is controlled to reach 0.1%-5%.
[0047] Similarly, when the secondary doping aid is selected from one or more of niobic acid, niobium pentoxide, niobium oxalate, and ammonium niobium oxalate; desalted water or hydrochloric acid or nitric acid with a molar concentration of 0.01-0.1% is used to dissolve the secondary doping aid, and the niobium ion concentration in the secondary doping aid solution is controlled to reach 0.1%-5%.
[0048] Preferably, in step S5, the dehydration and drying is carried out in a flash evaporation device, the flash evaporation temperature is 120-300° C., and the free water content of the flash dried material is controlled at 0.1-2%.
[0049] Preferably, in step S5, calcination is carried out in a rotary kiln, the calcination temperature of the rotary kiln is 500-800° C., and the calcination time is 0.5-6 h.
[0050] The present invention also provides a heterogeneously doped iron phosphate prepared by the above-mentioned preparation method, wherein the surface doping ion content of the heterogeneously doped iron phosphate is 1.2 to 1.7 times the core doping ion content.
[0051] The present invention also provides a heterogeneously doped lithium iron phosphate, which is prepared from the above-mentioned heterogeneously doped iron phosphate by a high-temperature solid phase method.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The present invention adopts the method of adding titanium ions to an iron source solution or a phosphorus source solution to uniformly dope the titanium ions into the interior of the iron phosphate particles, and then adds another layer of doping ions on the surface of the iron phosphate dihydrate after aging and crystallization by mixing and adding a secondary doping aid and drying and sintering. In this way, a shell-core structure of iron phosphate with a high surface doping ion content and a low internal doping ion content is formed. After the formation of lithium iron phosphate, the migration of lithium ions inside and on the surface of the unit cell is easier, and its electrical performance can reach 0.1C discharge gram capacity ≥162mAh / g, 1C discharge gram capacity ≥150mAh / g, 10C discharge gram capacity ≥135mAh / g, and excellent capacity and rate performance.
[0054] (2) The present invention introduces titanium ions by removing impurities from the by-product ferrous sulfate of titanium dioxide and then adding a doping aid. This can not only reduce costs, but also avoid the problem of uneven doping caused by the co-precipitation of non-ionic titanium in the original ferrous sulfate into ferric phosphate, which cannot effectively replace the iron element in the unit cell structure.
[0055] (3) The present invention adopts a microchannel tubular reactor as a reactor, which can achieve rapid and uniform generation of iron phosphate and effectively ensure uniform replacement of iron by titanium.
[0056] (4) The present invention controls the iron salt solution and hydrogen peroxide in the tubular reactor to be slightly excessive, which is beneficial to stably control the combination of trivalent iron ions and phosphate radicals, avoids the formation of precipitation of ferrous ions, and affects the quality of iron phosphate. Further, after the reaction is completed, a homogenizing reactor is used as a further reaction of the material at the outlet of the carrying reactor, and the amount of phosphate is further supplemented in the homogenizing reactor, so that the unreacted iron salt solution can continue to react, promote the continued growth of iron phosphate crystals, effectively control the particle size of iron phosphate, and improve the subsequent washing efficiency.
[0057] (5) The heterogeneously doped iron phosphate prepared by the present invention is used to prepare lithium iron phosphate by a high-temperature solid phase method. The secondary doping elements that have been calcined and evenly distributed on the surface of the heterogeneously doped iron phosphate particles are further melted and homogenized during the preparation of lithium iron phosphate, and are better dispersed in the lithium iron phosphate material, ensuring that the Li + Uniform migration path.
[0058] (6) The entire process of the present invention is simple and controllable, with low energy consumption, stable quality, low cost, and easy to promote and apply in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a SEM image of the heterogeneously doped iron phosphate used in Experimental Group 5 in the examples of the present application;
[0060] Figure 2 This is a SEM image of the lithium iron phosphate prepared in Experimental Group 5 in the examples of the present application. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0062] Example 1
[0063] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which specifically includes the following steps:
[0064] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 3.8, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 1000 ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0065] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.65:1.1 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.0, the reaction temperature is 50°C, the reaction time is 1 hour, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0066] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 12%, and add 85% phosphoric acid (10% by solid mass) to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 2 hours to prepare a slurry containing titanium-doped ferric phosphate dihydrate.
[0067] S4 secondary doping: adding a secondary doping auxiliary agent, nano-rutile titanium dioxide, to the slurry containing titanium-doped dihydrate iron phosphate in step S3 and uniformly mixing them, wherein the amount of nano-rutile titanium dioxide added is calculated according to controlling the titanium content in the heterogeneously doped iron phosphate to further reach 3000 ppm, filtering and washing after the mixing is completed, and preparing the secondary doped dihydrate iron phosphate;
[0068] S5 drying and calcination: the secondary doped ferric phosphate dihydrate prepared in step S4 is flash dried and dehydrated, the flash temperature is controlled at 260°C, and the free water content of the flash dried material is controlled at 0.5%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 700°C, and the calcination time is 3.0 hours, to promote further surface fusion of the secondary doping material and the ferric phosphate, and to prepare the heterogeneous titanium-doped ferric phosphate of this embodiment.
[0069] Example 2
[0070] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0071] In step S1, when preparing the titanium-containing ferrous sulfate solution, titanium tetrachloride in Example 1 is replaced by titanyl sulfate.
[0072] Example 3
[0073] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0074] In step S1, when preparing the titanium-containing ferrous sulfate solution, tetrabutyl titanate is used to replace the titanium tetrachloride in Example 1.
[0075] Example 4
[0076] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0077] In step S1, when preparing the titanium-containing ferrous sulfate solution, titanium citrate is used instead of the titanium tetrachloride in Example 1.
[0078] Example 5
[0079] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0080] In step S1, the amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous iron phosphate to be 500 ppm;
[0081] In step S4, the amount of nano-rutile titanium dioxide added is calculated based on controlling the titanium content in the heterogeneously doped iron phosphate to further reach 2500 ppm.
[0082] Example 6
[0083] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0084] In step S1, the amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous iron phosphate to be 3000 ppm;
[0085] In step S4, the amount of nano-rutile titanium dioxide added is calculated based on controlling the titanium content in the heterogeneously doped iron phosphate to further reach 5000 ppm.
[0086] Example 7
[0087] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0088] In step S4, the amount of nano-rutile titanium dioxide added is calculated based on controlling the titanium content in the heterogeneously doped iron phosphate to further reach 1500 ppm.
[0089] Example 8
[0090] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 1 only in that:
[0091] In step S4, the amount of nano-rutile titanium dioxide added is calculated based on controlling the titanium content in the heterogeneously doped iron phosphate to further reach 4000 ppm.
[0092] Example 9
[0093] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which specifically includes the following steps:
[0094] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 5.5, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 1000 ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0095] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.8:1.4 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.05, the reaction temperature is 55°C, the reaction time is 1.5 hours, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0096] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 15%, and add 85% phosphoric acid with a solid mass of 14% to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 1 hour to prepare a slurry containing titanium-doped ferric phosphate dihydrate.
[0097] S4 secondary doping: adding a secondary doping auxiliary agent, nano-anatase titanium dioxide, to the slurry containing titanium-doped dihydrate iron phosphate in step S3 and uniformly mixing them. The amount of nano-anatase titanium dioxide added is calculated according to controlling the titanium content in the heterogeneously doped iron phosphate to further reach 3000 ppm. After the mixing is completed, filtering and washing are performed to prepare secondary doped dihydrate iron phosphate;
[0098] S5 drying and calcination: the secondary doped ferric phosphate dihydrate prepared in step S4 is flash dried and dehydrated, the flash temperature is controlled at 120°C, and the free water content of the flash dried material is controlled at 2%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 800°C, and the calcination time is 6.0 hours, to promote further surface fusion of the secondary doping material and the ferric phosphate, and to prepare the heterogeneous titanium-doped ferric phosphate of this embodiment.
[0099] Example 10
[0100] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which specifically includes the following steps:
[0101] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 2.8, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 1000 ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0102] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.55:1.0 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:0.95, the reaction temperature is 45°C, the reaction time is 1.5 hours, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0103] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 8%, and add 8% 85% phosphoric acid with a solid mass% into the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 90°C and the crystallization time to 2 hours to prepare a slurry containing titanium-doped ferric phosphate dihydrate.
[0104] S4 secondary doping: adding a secondary doping auxiliary agent, metatitanic acid, to the slurry containing titanium-doped dihydrate iron phosphate in step S3 and uniformly mixing, wherein the amount of metatitanic acid added is calculated according to controlling the titanium content in the heterogeneously doped iron phosphate to further reach 3000 ppm, filtering and washing after the mixing is completed to prepare the secondary doped dihydrate iron phosphate;
[0105] S5 drying and calcination: the secondary doped ferric phosphate dihydrate prepared in step S4 is flash dried and dehydrated, the flash temperature is controlled at 300°C, and the free water content of the flash dried material is controlled at 0.1%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 500°C, and the calcination time is 4.0 hours, to promote further surface fusion of the secondary doping material and the ferric phosphate, and to prepare the heterogeneous titanium-doped ferric phosphate of this embodiment.
[0106] Embodiment 11
[0107] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which specifically includes the following steps:
[0108] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 3.8, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 1000 ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0109] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.65:1.1 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.0, the reaction temperature is 50°C, the reaction time is 1 hour, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0110] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 12%, and add 85% phosphoric acid (10% by solid mass) to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 2 hours. After filtering and washing, the titanium-doped ferric phosphate dihydrate solid phase is prepared.
[0111] S4 secondary doping: dissolving the secondary doping auxiliary agent ammonium metavanadate in desalted water to prepare a vanadium-containing solution, controlling the vanadium ion concentration to 3%; spraying the vanadium-containing solution in an atomized form on the titanium-doped dihydrate iron phosphate solid phase prepared in step S3 under stirring. The amount of the secondary doping auxiliary agent ammonium metavanadate added controls the vanadium doping amount in the final heterogeneously doped iron phosphate to be 2000ppm.
[0112] S5 drying and calcination: the secondary doped ferric phosphate dihydrate prepared in step S4 is flash dried and dehydrated, the flash temperature is controlled at 260°C, and the free water content of the flash dried material is controlled at 0.5%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 700°C, and the calcination time is 3.0 hours, to promote further surface fusion of the secondary doping material and the ferric phosphate, and to prepare the heterogeneous titanium-doped ferric phosphate of this embodiment.
[0113] Example 12
[0114] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 11 only in that:
[0115] The method of adding the secondary doping auxiliary agent vanadium in step S4 is different: in this embodiment, the vanadium-containing solution in an atomized form and the titanium-doped iron phosphate dihydrate solid phase prepared in step S3 are added to the flash evaporation device in step S5 for dehydration and drying.
[0116] Example 13
[0117] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 12 only in that:
[0118] The amount of vanadium added as the secondary doping aid in step S4 is different: the amount of ammonium metavanadate added as the secondary doping aid in this embodiment controls the final vanadium doping amount in the heterogeneously doped iron phosphate to be 500 ppm.
[0119] Embodiment 14
[0120] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 12 only in that:
[0121] The amount of vanadium added as the secondary doping aid in step S4 is different: the amount of ammonium metavanadate added as the secondary doping aid in this embodiment controls the final vanadium doping amount in the heterogeneously doped iron phosphate to be 3000 ppm.
[0122] Embodiment 15
[0123] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 12 only in that:
[0124] The selection of the secondary doping aid in step S4 is different: the secondary doping aid in this embodiment selects vanadium pentoxide to replace the ammonium metavanadate in Example 12.
[0125] Example 16
[0126] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which differs from Embodiment 12 only in that:
[0127] The selection of the secondary doping aid in step S4 is different: the secondary doping aid in this embodiment selects vanadyl sulfate instead of the ammonium metavanadate in Example 12.
[0128] Embodiment 17
[0129] This embodiment provides a method for preparing heterogeneously doped iron phosphate, which specifically includes the following steps:
[0130] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 3.8, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 1000 ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0131] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.65:1.1 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.0, the reaction temperature is 50°C, the reaction time is 1 hour, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0132] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 12%, and add 85% phosphoric acid (10% by solid mass) to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 2 hours. After filtering and washing, the titanium-doped ferric phosphate dihydrate solid phase is prepared.
[0133] S4 secondary doping solution configuration: The secondary doping auxiliary agent niobium oxalate is dissolved in desalted water to prepare a niobium-containing solution, and the niobium ion concentration is controlled to reach 3%; the amount of secondary doping auxiliary agent niobium oxalate is added to control the niobium doping amount in the final heterogeneous doped iron phosphate to be 2000ppm.
[0134] S5 drying and calcining: the secondary doping solution prepared in step S4 is added to a flash evaporation device in an atomized form and the titanium-doped dihydrate ferric phosphate prepared in step S3 for flash drying and dehydration, the flash temperature is controlled at 260°C, and the free water content of the flash dried material is controlled at 0.5%; then it is added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 700°C, and the calcination time is 3.0 hours, to promote further surface fusion of the secondary doping material and the ferric phosphate, and prepare the heterogeneous titanium-doped ferric phosphate of this embodiment.
[0135] Comparative Example 1
[0136] This comparative example provides a method for preparing doped iron phosphate, which specifically comprises the following steps:
[0137] Preparation of S1 raw material liquid: prepare an iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 3.8, and remove the impurity ions carried in the ferrous sulfate; add titanium tetrachloride to the ferrous sulfate solution after filtration and separation, and obtain a titanium-containing ferrous sulfate solution after homogenization. The amount of titanium tetrachloride added is calculated based on controlling the titanium content in the amorphous ferric phosphate to 3000ppm; prepare a phosphorus source solution with industrial-grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for standby use.
[0138] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and titanium-containing ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.65:1.1 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is supplemented and added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.0, the reaction temperature is 50°C, the reaction time is 1 hour, the slurry is filtered and washed to obtain titanium-doped amorphous iron phosphate.
[0139] S3 aging and crystallization: add water to the titanium-doped amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 12%, and add 85% phosphoric acid (10% by solid mass) to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 2 hours. Filter and wash to prepare titanium-doped ferric phosphate dihydrate.
[0140] S4 drying and calcination: The titanium-doped ferric phosphate dihydrate prepared in step S3 is flash dried and dehydrated, the flash temperature is controlled at 260°C, and the free water content of the flash dried material is controlled at 0.5%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 700°C, and the calcination time is 3.0 hours to prepare the doped ferric phosphate of this embodiment.
[0141] Comparative Example 2
[0142] This comparative example provides a method for preparing iron phosphate, which specifically comprises the following steps:
[0143] Preparation of S1 raw material liquid: prepare the iron source solution with ferrous sulfate heptahydrate, a by-product of titanium dioxide, and use ammonia water to neutralize the residual sulfuric acid in the ferrous sulfate, adjust the pH value of the solution to 3.8, and remove the impurity ions carried by the ferrous sulfate; prepare the phosphorus source solution with industrial grade monoammonium phosphate, and use ammonia water to adjust the pH value of the phosphorus source solution to 7.0 for use.
[0144] S2 mixing reaction: the phosphorus source solution, hydrogen peroxide and ferrous sulfate solution prepared in step S1 are heated to 30°C, and added to a microchannel tubular reactor at a molar ratio of P:H2O2:Fe=1.0:0.65:1.1 for rapid reaction; the slurry after the reaction enters a homogenizing reactor, and the remaining part of the phosphorus source solution is added to the homogenizing reactor at a P:Fe element ratio of 1.0:1.0, the reaction temperature is 50°C, the reaction time is 1 hour, the slurry is filtered and washed to obtain amorphous iron phosphate.
[0145] S3 aging and crystallization: add water to the amorphous ferric phosphate prepared in step S2 to obtain a slurry with a solid content of 12%, and add 85% phosphoric acid (10% by solid mass) to the slurry; gradually heat the slurry for aging and crystallization, and the crystallization conditions control the crystallization temperature to 95°C and the crystallization time to 2 hours to prepare ferric phosphate dihydrate.
[0146] S4 drying and calcination: The ferric phosphate dihydrate prepared in step S3 is flash dried and dehydrated, the flash temperature is controlled at 260°C, and the free water content of the flash dried material is controlled at 0.5%; it is then added to a rotary kiln for high-temperature calcination, the rotary kiln calcination temperature is 700°C, and the calcination time is 3.0 hours to prepare the ferric phosphate of this embodiment.
[0147] Experimental example
[0148] The heterogeneously doped iron phosphate prepared in Examples 1-17, the doped iron phosphate prepared in Comparative Example 1, and the iron phosphate prepared in Comparative Example 2 were used to prepare a lithium iron phosphate positive electrode material according to the following method:
[0149] Lithium carbonate and iron phosphate are mixed according to the requirement of Li:Fe:P molar ratio of 1.03:1:1.03 to obtain raw materials, the powder material obtained by the above ingredients and citric acid accounting for 15% of the total mass of the raw materials are mixed and dissolved in deionized water, the solid content is adjusted to 45%, and then wet grinding is carried out to make the finished slurry particle size D50 of 350±10nm; then the slurry is pumped into a spray drying equipment through a diaphragm pump for drying and granulation; then the dried material is sintered in a kiln, wherein the sintering temperature is 780°C and the insulation time is about 10 hours, to obtain the corresponding lithium iron phosphate positive electrode material.
[0150] At the same time, the iron phosphate prepared in Comparative Example 1 and Comparative Example 2 was used to prepare lithium iron phosphate positive electrode material by the following method:
[0151] Lithium carbonate and iron phosphate are mixed according to the requirement of Li:Fe:P molar ratio of 1.03:1:1.03 to obtain raw materials, and 3000 ppm of titanium dioxide (calculated based on lithium iron phosphate products) is added; the powder material obtained by the above ingredients and citric acid accounting for 15% of the total mass of the raw materials are mixed and dissolved in deionized water, the solid content is adjusted to 45%, and then wet grinding is carried out to make the finished slurry particle size D50 350±10nm; then the slurry is pumped into a spray drying equipment through a diaphragm pump for drying and granulation; then the dried material is sintered in a kiln, wherein the sintering temperature is 780°C and the insulation time is about 10 hours to obtain the corresponding lithium iron phosphate positive electrode material.
[0152] The parameters of the lithium iron phosphate positive electrode material prepared above were measured for 0.1C discharge gram capacity, 1C discharge gram capacity, and 10C discharge gram capacity. The measurement results are shown in Table 1 below:
[0153] Table 1 Electrical performance data of each sample
[0154]
[0155] From the results in Table 1 above, we can know that:
[0156] (1) Experimental group 1 is a lithium iron phosphate positive electrode material without any doping, and its electrical performance is the worst, which confirms the role of doping modification in promoting the electrical performance of lithium iron phosphate positive electrode materials.
[0157] (2) Experimental Group 2 only performed titanium doping once in the preparation of iron phosphate by co-precipitation of titanium ions and iron phosphate; Experimental Group 3 only performed titanium doping by adding titanium in the form of solid mixing during the preparation of lithium iron phosphate; Experimental Group 5 used the lithium iron phosphate prepared by the iron phosphate obtained by the preparation method of the present application for double doping. By comparing the data of Experimental Groups 2, 3 and 5, it can be seen that when the doping elements are consistent and the doping amount is the same, the electrical properties of the lithium iron phosphate prepared by the iron phosphate prepared by the preparation method of the present application are far better than the electrical properties of the prior art that is only doped once or only solid-phase doped during the preparation of lithium iron phosphate. This shows that the iron phosphate prepared by the preparation method of the present application can not only ensure the uniform distribution of titanium ions inside the iron phosphate, but also form more Li on the surface of the iron phosphate particles than inside. + Migration channel, better adapted to Li + The restriction that migration becomes more difficult toward the surface further promotes the good electrical properties of the prepared lithium iron phosphate positive electrode material.
[0158] (3) Experimental group 4 was doped with titanium only once in the preparation of iron phosphate by co-precipitation of titanium ions and iron phosphate, and was doped twice in the preparation of lithium iron phosphate by solid phase doping; experimental group 5 was doped once in the preparation of iron phosphate and was doped twice before calcination after crystallization. By comparing the results of experimental group 4 and experimental group 5, it can be seen that the electrical performance of the lithium iron phosphate positive electrode material of experimental group 5 is better than that of experimental group 4, indicating that the method of performing secondary doping after the crystallization is completed by the present application can make the iron phosphate precursor itself form a stable shell-core structure doping structure, and the lithium iron phosphate unit cell formed later can effectively realize Li from the core to the surface in the unit cell structure unit. + The electrical properties of the entire material are stable and excellent.
[0159] (4) The difference between Experimental Group 5 to Experimental Group 8 is that different primary doping agents are used in the preparation of iron phosphate. By comparing the data results of Experimental Group 5 to Experimental Group 8, it can be seen that when different doping agents are selected for doping, the amount of doping ions that can enter the iron phosphate is different, thereby affecting the performance of the final product.
[0160] (5) The difference between Experimental Group 9 and Experimental Group 12 lies in the different amounts of doping during the two times. By comparing the data results of Experimental Group 9 to Experimental Group 12, it can be seen that the greater the doping amount, the better the electrical properties of the obtained iron phosphate. The greater the doping amount, the more impurities in the lithium iron phosphate will be, which will in turn affect the electrical properties of the lithium iron phosphate. When the doping amounts of the first doping and the second doping reach a certain reasonable ratio, the electrical properties of the obtained iron phosphate are optimal.
[0161] (6) Experimental Groups 15 to 20 all used vanadium as the secondary doping element, and used different mixing forms and different doping amounts for vanadium doping. The results showed that the use of vanadium as the secondary doping element can obtain the same level of electrical properties as titanium doping.
[0162] (7) Experimental group 21 uses niobium as the secondary doping element. The results show that the use of niobium as the secondary doping element can achieve the same level of electrical properties as titanium doping.
[0163] Figure 1 This is a SEM image of the heterogeneously doped iron phosphate used in Experimental Group 5 (i.e., the heterogeneously doped iron phosphate prepared in Example 1). Figure 2 This is the SEM image of lithium iron phosphate further prepared in Experimental Group 5. Figure 1It can be concluded that the heterogeneously doped iron phosphate prepared by the method of the present invention has a flaky morphology of the iron phosphate grains as a whole, with columnar growth on the surface or edge of the flaky matrix. These columnar growths are secondary doping aids uniformly dispersed on the surface of the iron phosphate grains and partially penetrated into the surface of the iron phosphate grains, forming a stable shell doping. Further observation Figure 2 It can be seen that Figure 1 The lithium iron phosphate particles formed by high-temperature solid phase method have smooth surface and uniform particle size distribution. Figure 2 This is not shown in the figure, indicating that after further high-temperature calcination of the doped iron phosphate, the doping elements have been completely and evenly dispersed in the lithium iron phosphate product, forming a microstructure in which the surface migration channels are more than the core migration channels in the unit cell of the lithium iron phosphate, effectively promoting the uniform electrical performance improvement of the overall material.
Claims
1. A method for preparing heterogeneously doped iron phosphate, characterized in that: The steps include: S1. Preparation of raw material solution: prepare the iron source into an iron source solution, and prepare the phosphorus source into a phosphorus source solution; prepare a primary doping auxiliary agent containing titanium ions into a solution, add it to the iron source solution or the phosphorus source solution, mix well and set aside; S2 mixing reaction: adding the iron source solution containing titanium ions, the phosphorus source solution and the oxidant, or the phosphorus source solution containing titanium ions, the iron source solution and the oxidant prepared in step S1 to the reactor in proportion for rapid reaction; after the reaction, filtering and washing the slurry to prepare titanium-doped amorphous iron phosphate; S3 aging and crystallization: adding water to the titanium-doped amorphous ferric phosphate prepared in step S2 to prepare a slurry, and adding a phosphoric acid solution to the slurry; gradually heating the slurry to perform aging and crystallization, and after the crystallization is completed, titanium-doped ferric phosphate dihydrate is prepared; S4 secondary doping: uniformly adding a secondary doping aid to the titanium-doped ferric phosphate dihydrate prepared in step S3 to form a secondary doping ferric phosphate dihydrate; the secondary doping aid contains a secondary doping element, and the secondary doping element is selected from at least one of titanium, vanadium or niobium; S5 drying and calcining: the secondary doped ferric phosphate dihydrate obtained in step S4 is dehydrated and dried, and then calcined at high temperature to form heterogeneous doped ferric phosphate.
2. The method for preparing heterogeneously doped iron phosphate according to claim 1, characterized in that: The primary doping aid is one or more of titanyl sulfate, titanium tetrachloride, tetrabutyl titanate, and titanium citrate.
3. The method for preparing heterogeneously doped iron phosphate according to claim 1, characterized in that: The dosage of the primary doping auxiliary agent is controlled so that the titanium content in the obtained titanium-doped amorphous iron phosphate is 500-3000 ppm.
4. The method for preparing heterogeneously doped iron phosphate according to claim 1, characterized in that: The preparation method of the iron source solution in step S1 is: prepare a solution of ferrous sulfate produced as a by-product of titanium dioxide, adjust the pH value to 2.8-5.5 with a pH adjuster to perform a decontamination reaction, and after the decontamination reaction is completed, filter and separate the precipitate to obtain the iron source solution.
5. The method for preparing heterogeneously doped iron phosphate according to claim 1, characterized in that: The mixing reaction in step S2 is carried out in a microchannel tubular reactor.
6. The method for preparing heterogeneously doped iron phosphate according to claim 5, characterized in that: The molar ratio of the phosphorus source, oxidant and iron source added to the microchannel tubular reactor satisfies: P: oxidant: Fe = 1.0: 0.55-0.8: 1.0-1.4; after the reaction is completed, the slurry first enters the homogenizing reactor, and the phosphorus source solution is continuously added to the homogenizing reactor, so that the final P: Fe involved in the reaction = 1: 0.95-1.05; after the reaction is completed, the slurry is filtered and washed to prepare titanium-doped amorphous iron phosphate.
7. The method for preparing heterogeneously doped iron phosphate according to any one of claims 1 to 6, characterized in that: The dosage of the secondary doping auxiliary agent is controlled so that the content of the secondary doping element in the final product heterogeneously doped iron phosphate is 500-3000 ppm.
8. The method for preparing heterogeneously doped iron phosphate according to claim 7, characterized in that: When the secondary doping element is titanium, the secondary doping aid is one or more of titanyl sulfate, titanium tetrachloride, tetrabutyl titanate, titanium citrate, nano rutile titanium dioxide, nano anatase titanium dioxide, and metatitanic acid; preferably, the secondary doping aid is one or more of nano rutile titanium dioxide, nano anatase titanium dioxide, and metatitanic acid; When the secondary doping element is vanadium, the secondary doping aid is one or more of ammonium metavanadate, vanadium pentoxide, and vanadyl sulfate; When the secondary doping element is niobium, the secondary doping aid is one or more of niobic acid, niobium pentoxide, niobium oxalate, and ammonium niobium oxalate.
9. The method for preparing heterogeneously doped iron phosphate according to claim 8, characterized in that: In step S4, when the secondary doping aid is insoluble in water, the secondary doping aid is added in solid phase form, directly added to the slurry containing titanium-doped ferric phosphate dihydrate obtained after the crystallization in step S3, and then the slurry is filtered and washed to obtain the secondary doped ferric phosphate dihydrate; In step S4, when the secondary doping aid is dissolved in water, the secondary doping aid is added in the form of a solution, and the slurry containing titanium-doped iron phosphate dihydrate after the crystallization in step S3 is filtered and washed to obtain a titanium-doped iron phosphate dihydrate solid phase; the solution containing the secondary doping aid is directly added to the titanium-doped iron phosphate dihydrate solid phase in an atomized form, or the solution containing the secondary doping aid is introduced into a dehydration and drying device in an atomized form together with the titanium-doped iron phosphate dihydrate solid phase to obtain the secondary doped iron phosphate dihydrate.
10. The method for preparing heterogeneously doped iron phosphate according to claim 9, characterized in that: In step S4, when the secondary doping aid is dissolved in water, the secondary doping aid is dissolved in desalted water or hydrochloric acid or nitric acid with a molar concentration of 0.01-0.1% to prepare a solution, and is added in the form of a solution.
11. The method for preparing heterogeneously doped iron phosphate according to claim 1, characterized in that: In step S5, the dehydration and drying step is carried out in a flash evaporation device at a flash evaporation temperature of 120 to 300°C.
12. A heterogeneously doped iron phosphate, characterized in that: Prepared by the preparation method according to any one of claims 1 to 11, the surface doping ion content of the heterogeneously doped iron phosphate particles is 1.2 to 1.7 times the core doping ion content.
13. A heterogeneously doped lithium iron phosphate, characterized in that: The heterogeneously doped iron phosphate described in claim 12 is prepared by a high-temperature solid phase method.
Citation Information
Patent Citations
Titanium-doped anhydrous iron phosphate material as well as preparation method and application thereof
CN117756076A
Preparation method of battery-grade titanium-doped iron phosphate
CN118495494A
Ball-shaped lithium-ion battery anode material doped with rare earth and method for making same
CN101013751A
Lithium iron phosphate material for lithium ion power battery, and preparation method thereof
CN104409688A
Preparation method and application of lithium iron phosphate / carbon composite material
CN114613965A
Cited By
Titanium-doped iron phosphate as well as preparation method and application thereof
CN120622435A